A post-conolain Viewing to Migration and Cultural Identity in Kiran Desai's The Inheritance of Loss (2006) - ZEROUALA, Douaa; Mouissa, Fattoum (Faculty of Letters and Foreign Languages Department of English, 2023)
Migration has a profound impact on identity construction, where migrants often have their traditional cultures and identities disrupted. Kiran Desai is one of the most popular authors that tackled the issues of migration and identity based on her life experiences as a migrant herself. Her novel The Inheritance of Loss (2016) offers a comprehensive exploration of the challenges and trials experienced by migrants in the aftermath of colonialism, as it also provides the challenges of getting exposed to new cultures that play a role in reshaping people’s identities. Thus, the dissertation raises a main question that explores the effects of migration that lead her protagonists to undergo identity crises. This research aims to provide descriptions and analysis concerning the trials they went through while figuring out their real identity, such as racism, marginalisation, psychological turmoil, and trauma, as they struggled to reconcile their original identities with the new cultural environments they were exposed to. Based on this explanation, this research uses cultural, historical, and psychoanalytical approaches in order to provide a clear explanation of the psychological effects of colonialism, in addition to the applied and descriptive methods that help in applying certain theories to describe the struggles faced by migrants in the west. In view of this, the final results show that getting exposed to a new environment can change migrants' identities as they adopt the practices and values of the host culture, leading to a gradual transformation in their perception of self, and aligning more closely with the norms of the host culture. Moreover, migrants may feel pressured to assimilate into the new culture as a means of coping with racism, which further triggers their identity crisis and reformation